A Moroccan woman with severe electrolyte disorder. (3rd August 2010) - Pedrazzini, B; Favrat, B; Lehr, H-A; Bodenmann, P
Abstract : The case of a Moroccan woman, age 25, who came into the emergency department with clinical tetany, is presented. She had experienced muscle spasms and paresthaesia of the upper limb over the previous few days. She had also experienced major diarrhoea for the previous 3 weeks. Investigations revealed a severe electrolyte disorder.